The Impact of Premature Rupture of Membranes (PROM) and Low Birth Weight (LBW) Infant Outcomes to the Survival Rate : Hubungan Ketuban Pecah Dini (KPD) dengan Luaran Bayi Berat Badan Lahir Rendah (BBLR) terhadap Survival rate setelah Satu Minggu Dilahirkan - Hasanuddin; Dannu Wijaya; Dora Darusalam (Indonesian Journal of Obstetrics and Gynecology, 2022)
Abstract Objective: To determine the impact of premature rupture of membranes and the outcome of low birth weight on the survival rate one week after birth in RSUDZA Banda Aceh. Method: This study used an observational analytic study with a prospective cohort study design. The research samples were 84 samples that met the inclusion and exclusion criteria. The data source used was primary data obtained by direct examination by weighing the newborn at birth and during visits. Results: There was an impact of premature rupture of membranes and the outcome of low birth weight on the survival rate of infants after one week. The results showed that the p-value <0.000. The lowest neonatal survival rate was in the group weighing less than 1000 grams, namely 0%. Weight group 1000 grams to 1500 grams with a survival rate of 55% and group weight 1500 grams to 2500 grams with a survival rate of 95%. Discussion: There was an impact of premature rupture of membranes and the outcome of low birth weight on the survival rate one week after birth in RSUDZA Banda Aceh. Keywords: low birth weight (LBW), preterm premature rupture of membranes, survival rate. Abstrak Tujuan : Untuk mengetahui dampak ketuban pecah dini dengan luaran berat badan lahir rendah terhadap survival rate satu minggu setelah dilahirkan di RSUDZA Banda Aceh. Metode: Penelitian ini menggunakan studi analitik observasional dengan desain penelitian kohort prospektif. Sampel penelitian sebanyak 84 sampel yang memenuhi kriteria inklusi dan eksklusi. Sumber data yang digunakan adalah data primer yang diperoleh dengan cara pemeriksaan langsung dengan penimbangan bayi saat baru lahir dan ketika kunjungan. Hasil: Ada dampak ketuban pecah dini dengan luaran berat badan lahir rendah terhadap survival rate bayi setelah satu minggu didapatkan hasil bahwa p-value <0,000. Survival rate neonatal terendah pada kelompok berat badan di bawah 1000 gram yakni 0%. Kelompok berat badan 1000 gram sampai di bawah 1.499 gram memiliki survival rate 55% dan kelompok berat badan 1.500 gram sampai 2.499 gram memiliki angka survival rate 95%. Diskusi: Ada dampak ketuban pecah dini dengan luaran berat badan lahir rendah terhadap survival rate satu minggu setelah bayi dilahirkan di RSUDZA Banda Aceh. Kata kunci: berat badan lahir rendah (BBLR), ketuban pecah dini, survival rate.